COVID-19 pandemic unmasking cardiovascular risk factors and non-communicable diseases among migrant workers: a cross-sectional study in Singapore - Natalie Liling Woong; Amanda Yun Rui Lam; Shaikh Abdul Matin Mattar; Ling Zhu; Tharmmambal Balakrishnan; Juliana Yin Li Kan; Orlanda Qi Mei Goh; Yuyang Tan; Shalini Sri Kumaran; Koin Lon Shum; Guozhang Lee; Chiara Jiamin Chong; et al. (BMJ Open)
Objectives This study aims to report the prevalence of cardiovascular risk factors (CVRFs) and other non-communicable diseases among migrant workers in Singapore admitted for COVID-19 infection, to highlight disease burden and the need for changes in health screening and healthcare delivery in this unique population.Setting The study was conducted in the largest tertiary hospital in Singapore.Design Retrospective cross-sectional study.Participants 883 migrant workers who had mild or asymptomatic COVID-19 infection admitted to three isolation wards between 6 April 2020 and 31 May 2020 were included in this study.Outcome measures The outcome measures were the prevalence of pre-existing and newly diagnosed comorbid conditions and the prevalence of CVRFs—diabetes mellitus, hypertension and hyperlipidaemia—and non-communicable diseases at the time of discharge. The OR of having specific CVRFs depending on country of origin was generated via multivariate logistic regression analysis.Results The median age of our study population was 45 years. 17.0% had pre-existing conditions and 25.9% received new diagnoses. Of the new diagnoses, 15.7% were acute medical conditions and 84.3% chronic medical conditions. The prevalence of CVRFs was higher in Southeast Asian and South Asian migrant workers compared with Chinese. The prevalence of non-communicable diseases on discharge was highest among Southeast Asians (49.4%).Conclusions The COVID-19 outbreak in a large number of migrant workers in Singapore unmasked a significant disease burden among them, increasing stakeholders’ interests in their welfare. Moving forward, system-level changes are necessary to deliver healthcare sustainably and effect improvements in migrant workers’ health.